MicroRNA-365 suppresses cell growth and invasion in esophageal squamous cell carcinoma by modulating phosphoserine aminotransferase 1 - Sun, Changjiang (Cancer Manag Res, 2018)
BACKGROUND: A number of studies have indicated that expression of miRNA-365 (miR-365) is suppressed in various cancers, suggesting its cancer-suppressive role. In the present investigation, we evaluated the regulation and character of miR-365 in human esophageal squamous cell carcinoma (ESCC). PATIENTS AND METHODS: The tumor tissues and adjacent nontumor tissue samples were collected from 30 patients having ESCC, and the expression levels of miR-365 were studied by quantitative real-time polymerase chain reaction (PCR). MTT and cell invasion by Matrigel assay were done to study the effect of miR-365 on proliferation and metastasis of ESCC cells. An in vivo tumor model was generated by inoculating ESCC cells subcutaneously into BALB nude mice. A study of various biomarkers such as quantitative polymerase chain reaction (qPCR), luciferase activity assay, and Western blot was done to confirm the targets of miR-365. RESULTS: In tumor tissues, a significant downregulation of miR-365 was observed versus the nontumor adjacent tissues and ESCC cells versus the selected esophageal endothelial cells. It was observed that higher expression levels of miR-365 inhibited the cell invasion, colony formation, growth in esophageal cancer cell lines in vitro, and tumor development in vivo. The study of biomarkers suggests involvement of phosphoserine aminotransferase 1 (PSAT1) as a favorable target for miR-365, and its abnormal expression inverted the miR-365-arbitrated suppression of invasion, viability, and epithelial–mesenchymal transition in esophageal cancer cells. A negative correlation existed with expression of miR-365 and PSAT1 in human esophageal cancer tissue samples. CONCLUSION: The study established that miR-365 exhibits tumor-suppressive action via regulating the levels of PSAT1 and leads to invasion and progressiveness of esophageal cancer.